Kajian kemahiran belajar dalam kalangan pelajar bidang pendidikan Universiti Utara Malaysia - Mohd Yusoff, Nurahimah; Osman, Rafisah; Shaari, Abdull Sukor; Ghazali, Mohd Izam (Universiti Utara Malaysia, 2012)
The aim of this research was to identify the relationship between study skills and academic achievement among the students in Universiti Utara Malaysia. A total of 112 undergraduate education students of SGDE 3133 Measurement and Evaluation in Education course at the School of Education and Modern Languages, Universiti Utara Malaysia, was involved in the study. The respondents comprised of 23 male and 89 female students.The study employed a set of questionnaire measuring on students’ study skills using four point scales. Study skills constructs used in this study are Attitude, Note Taking, Concentration and Retrieval, Memory, Reading, Writing, Time Management , and Exam Preparation. From the data that was analyzed, the students’ study skills level was found to be moderate (M=2.83. SD = .32) .The Pearson correlation test is applied to determine the relationship between study skills and academic achievement.The results of Pearson correlation test showed that there was a significant relationship between study skills and academic achievement ( r = .23, p< .5). Based on the findings, some suggestions to increase students academic performance and also recommendations for future research are provided in the study.